IMPLEMENTATION OF OPEN-ENDED PROBLEMS ON MATHEMATICAL PROBLEM-SOLVING SKILL OF ELEMENTARY SCHOOL STUDENTS - Diana Ermawati; Eka Zuliana (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2020)
AbstractThis research is a quasi-experimental research with the purpose to find out the effect of open ended problem on mathematical problem solving skill of elementary school students. The research was conducted on grade 5 students of Gemiring Kidul 1 and Gemiring Kidul 2 Elementary School. These two classes used for research have an equivalent level of skill. Elementary School 1 Gemiring Kidul as an experimental group with 21 students of grade 5 and Elementary School 2 Gemiring Kidul as a control group with 20 students of grade 5. This research has two variables; the independent variable is the implementation of open-ended problem, while the dependent variable is the skill to solve mathematical problems. Both groups were given a pre-test and post-test. The instrument used to measure the problem-solving ability was obtained through a description test of five questions that had been declared valid by experts. Data were analyzed using a t-test. The results of the research revealed that the average pre-test score was 54.62 to 82.29 after the post-test was done using the open-ended problem. The results of t-test calculations obtained tcount of 8.456 and ttable of 1.677 with a significance level of 0.05. The data can be interpreted that tcount> ttable, so H0 is rejected. This shows that learning by implementing open ended problems can significantly improve mathematical problem solving skill.Keywords: Open-Ended Problem; Mathematical Problem Solving